The Serratia sp. strain C2 confers tomato tolerance to high salt, virus infection and both stresses in combination - Sayahi, Naima; Sportelli, Giorgia; Carluccio, Anna Vittoria; Ebel, Chantal; Mechichi, Tahar; Cillo, Fabrizio; Hanin, Moez; Stavolone, Livia (Current plant biology, 2024)
Besides increasing plant growth, several Plant Growth Promoting Rhizobacteria (PGPR), can enhance tolerance to biotic and/or abiotic stresses of numerous plant species. While cultivated plants are frequently subject to combined stresses in the field, there is limited knowledge of the effect of PGPR on plants undergoing simultaneous stress conditions. Therefore, we tested the beneficial properties of the halotolerant PGPR Serratia sp. strain C2, previously shown to enhance salt stress tolerance in barley, on tomato plants exposed to salinity, to Potato Virus Y (PVY) infection, and both stresses simultaneously. In our experimental conditions, C2 inoculation improved tomato tolerance to salt stress and positively correlated with a 46–68 % decrease in the level of PVY RNA compared to non-inoculated tomato plants. Morphometric, physiological and biochemical analyses (e.g., chlorophyll, sugar and proline accumulation, oxidative stress status and NDVI) indicated that C2 treatments had beneficial effects on tomato growth under simple and combined stress conditions. This is the first report of a PGPR enhancing tolerance not only to individually induced salinity and PVY infection, but also to both stresses in combination. Moreover, the expression analysis of selected genes involved in stress responses and RNA silencing-mediated antiviral immunity suggests that C2 can interfere with distinct defence response pathways to enhance stress tolerance in tomato. These pioneering results support the perspective of using PGPR as multi-spectrum and multi-host biostimulants for improving plant growth and protection from biotic, abiotic, and combined stresses to promote sustainable crop production in the face of environmental changes. •The C2 PGPR improves tomato tolerance to simple and combined abiotic (salinity) and biotic (Potato Virus Y infection) stress treatments.•The C2-treated tomato plants show strong late suppression of PVY RNA accumulation under combined stress conditions.•The C2 PGPR can be used in broad-spectrum bioformulation to improve plant growth under a wide stress conditions to promote sustainable crop production.